Analysis of Factors Influencing the Adoption of the PELNI Mobile Application for Ship Ticket Purchases in Sorong using the Unified Theory of Acceptance and Use of Technology 2 - Regina Natalia Sianturi; Julius Panda Putra Naibaho; Alex De Kweldju (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2026)
This study aims to analyze the factors influencing the adoption of the PELNI Mobile application for ship ticket purchases using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) approach. The research employed a quantitative method with data collected through questionnaires distributed to users of the PELNI mobile application. The collected data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that Facilitating Conditions and Habit significantly influence the actual usage behavior of the PELNI mobile application. In contrast, Performance Expectancy, Effort Expectancy, Social Influence, Hedonic Motivation, and Price Value do not have a significant effect on usage intention. Furthermore, Behavioral Intention was also found to have no significant influence on actual usage behavior. These findings suggest that the adoption of the PELNI mobile application in the context of maritime transportation is more strongly influenced by the availability of supporting facilities and users’ habitual behavior than by perceived usefulness, ease of use, or social influence. This study is expected to contribute theoretically to the development of the UTAUT2 model and provide practical implications for the management of digital-based maritime transportation services.